Interim results of a first-in-human phase 1 study of Q-1802, a CLDN18.2/PD-L1 bsABs, in patients with relapsed or refractory solid tumors - Yk, Wang; Gong, Jifang; Sun, Yuping; Zhang, Jian; Ni, Shuqin; Hou, Jie; Chen, Xiaohua; Wang, Yusheng; Yu, Qin; Qu, Xiangdong; Du, Yejie; Wei, Li; et al. (Journal of clinical oncology, 2023)
382Background: Q-1802 is a humanized bispecific antibody that targets both the tumor -specific antigen CLDN18.2 and the immune checkpoint PD-L1. Q-1802 monotherapy dose-escalation study has been completed in China and dose-expansion study has enrolled 17 advanced subjects with advanced Gastric adenocarcinoma, pancreatic cancer, biliary tract cancer. Methods: This is a FIH, phase 1a/1b, multicenter, open label, single arm, dose escalation and dose expansion study of Q-1802, administered intravenously to 20-30 adult patients with resistant/refractory advanced or metastatic solid tumors who had failed standard therapies (NCT04856150). It aimed to evaluate the safety, tolerability, PK/PD profiles and preliminary efficacy of Q-1802 monotherapy. In the dose escalation phase (phase 1a), an accelerated titration followed by a 3+3 design was used to assess the safety and tolerability of Q-1802 (dose range 0.1 mg/kg to 20 mg/kg); and determine the maximum tolerated dose (MTD). Q-1802 was administered in a dose limiting toxicity (DLT) observation period followed by a Q2w treatment schedule. In the dose expansion phase (Phase 1b), one to two dose groups will be selected to enroll 9-23 Pts, including 3 negative CLDN18.2 expression and 6 positive CLDN18.2 expression in each group. Q-1802 was administered Q2w on a 14-day treatment cycle. Results: As of September 20, 2022, a total of 29 patients (median age 57.0 y; most patients received ≥3 prior regimens) were enrolled (12 Pts in phase 1a with DLT evaluation and 17 Pts in Phase 1b). The most common tumor types were GI cancers. There were no DLTs up to 20 mg/kg of Q-1802, inclusive. Two dose groups:10mg/kg and 20mg/kg were extended in Phase 1b study. Treatment-emergent adverse events were mostly grade 1-2 .The most common treatment related adverse events were Gastrointestinal AEs (89.7%, 26/29), including nausea 18/29 (62.1%), vomiting 18/29 (62.1%), abdominal pain 8/29 (27.6%), Gastroesophageal reflux disease 7/29 (24.1%). Grade 3 treatment-related AEs occurred 7/29 ( 24.1%), and gastrointestinal disease including nausea, vomiting has a higher percentage of 10.3% (3/29). Only one case has a grade 4 AE, hyponatremia, with a long term use of diuretics history. No death reported due to study related treatment. irAEs happened in 7 subjects, including abnormal thyroid function, fatigue, rash, arthritis. Most of irAEs were grade1-2. Among the 9 GIsubjects in the dose-expansion phase with CLDN18.2 positive expression who had measurable lesions and had received at least one post treatment tumor assessments, 2ptsachieved partial response and 4 achieved stable disease as the best overall response per RECIST1.1. Conclusions: Interim data from the present phase 1 study, demonstrate that Q-1802 has excellent preliminary safety, tolerability and preliminary anti-tumor activity up to doses of 20 mg/kg. The dose extension is still ongoing. Clinical trial information: NCT04856150.